2016
DOI: 10.1016/j.jpeds.2016.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Parental Decision-Making Preferences in Neonatal Intensive Care

Abstract: Characteristics of decisions influence preferences for control over medical decisions among parents of patients in the NICU. These insights may guide improvements in physician-parent communication and consent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 34 publications
(16 reference statements)
0
55
1
Order By: Relevance
“…In our study, parents contributed to decisions regarding respiratory support, infant feeding and discharge planning. Our finding that parents were not able to participate in the decision‐making process, especially in emergency situations, was echoed by another study that suggested that parents do not want to make decisions about their infant's care when the degree of urgency or required medical expertise is high . If this association is confirmed in future studies, healthcare teams will need to ensure that they respect the parents’ choices to defer from shared decision‐making in these situations.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In our study, parents contributed to decisions regarding respiratory support, infant feeding and discharge planning. Our finding that parents were not able to participate in the decision‐making process, especially in emergency situations, was echoed by another study that suggested that parents do not want to make decisions about their infant's care when the degree of urgency or required medical expertise is high . If this association is confirmed in future studies, healthcare teams will need to ensure that they respect the parents’ choices to defer from shared decision‐making in these situations.…”
Section: Discussionmentioning
confidence: 74%
“…Parents have expressed that making decisions about their infant's care allows them to feel closer to the infant , which makes it an important element of family‐centred care . Parents want to participate in decisions related to high perceived risks for the infant, decisions in which they have personal experience and in decisions that they perceive as part of the normal parental role . In our study, parents contributed to decisions regarding respiratory support, infant feeding and discharge planning.…”
Section: Discussionmentioning
confidence: 89%
“…For example, a high degree of urgency and a high level of required medical expertise have been associated with a parents' preference to delegate decisions. 52 Similarly, in oncology, parents have reported wanting the physician to assume decision-making when a child can probably be cured or when 1 best medical choice exists. 53 In contrast, parents prefer to maintain control of decisions when there is (1) high perceived risk, (2) experience with the decision, (3) involvement of foreign bodily fluids, and (4) a decision thought to be part of the normal parental role.…”
Section: Exploring Decision-making Preferencesmentioning
confidence: 99%
“…53 In contrast, parents prefer to maintain control of decisions when there is (1) high perceived risk, (2) experience with the decision, (3) involvement of foreign bodily fluids, and (4) a decision thought to be part of the normal parental role. 50,52 Families' style and expectations for decisional involvement and/or control may change over the course of the illness. Clinicians need to be aware and open to those changes.…”
Section: Exploring Decision-making Preferencesmentioning
confidence: 99%
“…Previously published work showed that decisional characteristics were associated with decision‐making preferences (e.g. for urgent decisions, NICU parents preferred medical team‐centred decision‐making) . Here, we sought to understand how parental factors may account for differences in decision‐making preferences.…”
Section: Model Of Relationship Between Parental Factors Decisional Fmentioning
confidence: 99%